Effect of Ti, Hf, Ni, Fe substitution on the hydrogen storage performance of porous ZrCo alloys - Yuan, Yingbo; Li, Zhenyang; Huang, Ziteng; Jiang, Zhao; Dong, Xiaohan; Qu, Linyu; Yao, Dong; Yu, Ronghai (International journal of hydrogen energy, 2025)
ZrCo alloys are regarded as the most promising hydrogen isotope storage materials to replace uranium in controlled fusion research. However, it is difficult to balance the kinetic and anti-disproportionation properties of conventional ZrCo alloys prepared by the smelting method. Here, we synthesize a series of porous ZrCoM (M = Ti, Hf, Ni, Fe) alloys using a wet-chemical method combining magnesiothermic reduction with electrospray deposition method, and systematically investigate the phase composition, microstructure, and hydrogen storage properties. Owing to the high specific surface area, high crystallinity, and elemental substitution effect, the porous Zr0.8Ti0.2Co simultaneously exhibits high hydrogen storage capacity (approach theoretical capacity), excellent anti-disproportionation properties (only 3.7% in 10 h) and ultrafast kinetics (reach maximum capacity within 30 s, one order of magnitude faster than smelting one). Moreover, the elemental substitution shortens the plateau width of the alloy, leading to improved thermodynamic properties as well. This work provides new insights into the development of ZrCo-based materials with excellent comprehensive hydrogen storage isotope properties for their engineering applications in nuclear fusion research. •Elemental substitution strategy is combined with wet chemical method.•The porous materials have high purity, crystallinity and specific surface area.•The as-synthesized materials show fast kinetics due to the small size effect.•Porous Zr0.8Ti0.2Co alloy exhibits excellent anti-disproportionation properties.